X*Y females exhibit steeper reproductive senescence in the African pygmy mouse - Jean-François Lemaître; Yann Voituron; Léa Herpe; Frédéric Veyrunes (Proceedings of the National Academy of Sciences, 2025)
A wave of studies has recently emphasized the influence of sex chromosomes on both lifespan and actuarial senescence patterns across vertebrates and invertebrates. Basically, the heterogametic sex (XY males in XX/XY systems or ZW females in ZW/ZZ systems) typically displays a lower lifespan and a steeper rate of actuarial senescence than the homogametic sex. However, whether these effects extend to the senescence patterns of other phenotypic traits or physiological functions is yet to be determined. Here, we investigated whether sex chromosomes modulate reproductive senescence using females from the African pygmy mouse ( Mus minutoides ). This biological model exhibits an odd sex determining system with a third, feminizing sex chromosome, X*, resulting in three distinct female genotypes (XX, X*X, or X*Y) that coexist in natural populations. We found that the rate of senescence in litter size at birth is much more pronounced in heterogametic X*Y females than in homogametic XX or X*X females that may support the unguarded X or toxic Y hypotheses and can be directly linked to the complex and unique X*Y phenotype. A decrease in neonatal survival with mother’s age has also been found, but this decline is not different between the three female genotypes.